A retrospective review to assess whether spinal fusion and scoliosis correction improved activity and participation for children with Angelman syndrome. (2nd September 2016) - Sewell, Mathew David; Wallace, Charles; Gibson, Alex; Noordeen, Hilali; Tucker, Stewart; Molloy, Sean; Lehovsky, Jan
Abstract: Objective : This study investigates outcome of scoliosis treatment for 11 children with Angelman syndrome (AS), with particular focus on activity, participation and the musculoskeletal factors that may affect these outcomes. Methods : Retrospective review of medical records, radiographs and questionnaires administered to caregivers of 11 children (8M:3F) with AS and scoliosis. Six underwent observational treatment during childhood and five underwent spinal fusion. The Activities Scale for Kids (ASKp) questionnaire was used to measure activity and participation. Questionnaire and radiographic data were recorded over a 2 year period. Results : In the observational group, scoliosis increased from 31° to 46°. Mean ASKp decreased from 13.8 to 11.9 ( p = 0.06). In the operative group, scoliosis decreased from 68° to 29°. Mean ASKp increased from 11.4 to 15.9 ( p < 0.01). There was also a reduction in spinal-related pain and mean number of hospital admissions for chest infection. However, there was a 60% major complication rate. There was no difference in mobility, GMFCS level, feeding or communication in either group before or after treatment. Conclusion : In children with significant scoliosis and AS, spinal fusion was associated with a small improvement in activity and participation, reduction in pain and a decrease in frequency of severe chest infections. Non-operative treatment resulted in progression of scoliosis during childhood and decrease in activity.